Matrix of Possibilities and contemporary Transformation in the Renovation of Ceramics (Al-Academy, 2024)
This study aims to explore contemporary solutions for the renovation of ceramics’ maser pieces through the use of matrix of possibilities which implies philosophic aspects that surpasses the preservation of ceramics, treatment and maintenance of the same. Such process uses the techniques of renovation for such ceramics already damaged thus transforming such damage to added-value to its beauty based on descriptive analytical methodology.Among the results achieved by this study is that the renovation of modern ceramics differs from such renovations aimed to renovate old ceramics by using the matrix of possibilities which allows the creation of contemporary ceramics that implies artistic and philosophic dimensions.Based on the results of this study, the author outlined her recommendations, among of which is the matrix of possibilities which is recommended by artists and artifacts specialists. In addition, it is imperative to supply libraries and competent authorities with such recommendations being of para importance in terms of adopting contemporary thoughts through such matrix so to create innovative and creative solutions in the field of ceramics renovation. Furthermore, it is advisable to hold seminars and workshops designed for renovation concepts aimed to revive the beauty of ceramic master pieces but in contemporary way, as well as making use of interim studies.